Differences in The Lexical and Pragmatic Meaning of The Word "Sangu" in Sundanese and Javanese - Sayyidah Nur Latifah; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The difference in the meaning of vocabulary between regional languages is an interesting linguistic phenomenon to study, especially in words that have the same form but are used in different language systems. One example of this phenomenon is the word sangu in Sundanese and Javanese. This study aims to analyze the differences in the lexical and pragmatic meanings of the word sangu in both languages. This study uses a qualitative descriptive method with a semantic and pragmatic approach. The research data was obtained from Sundanese and Javanese dictionaries and examples of speech from speakers in the context of everyday interactions. The results show that lexically, the word sangu in Sundanese is generally interpreted as ‘rice’ or ‘staple food’, while in Javanese, the word sangu is more often used to refer to ‘provisions’ in general. Pragmatically, these differences in meaning are influenced by the context of use, cultural background, and language habits of the speakers. These findings indicate that understanding the meaning of words across regional languages requires attention to linguistic and cultural aspects in order to reduce the potential for misunderstanding in communication.